Detection of Non-transferable vanC1 and vanC2/3 Genes in Vancomycin Resistant Enterococci Isolated from Freshwater Fish Collected from Retail Markets: Detection of vanC1 and vanC2/3 Genes in VRE - Kumar, Anil; Dwivedi, Arti; Soni, Mayank; Sahu, Vikash; Imran, Mohd; Kumar, Chandra Bhushan; Pradhan, P. K.; Sarkar, U. K.; Rathore, Gaurav (Fishery Technology, 2024)
Enterococci are opportunistic pathogens that can cause life-threatening infections like nosocomial endocarditis, bacteremia, wound infection and urinary tract infection in humans. Vancomycin resistant enterococci (VRE) carrying vanA and vanB genes are recognized by World Health Organization (WHO) as high-risk category organisms. The aim of this study was to ascertain the status of VRE in freshwater fish being sold in retail fish markets for human consumption, and document the molecular mechanism of their vancomycin resistance. A total of 60 gill/muscle swabs collected from freshwater fish were enriched in bile esculin azide broth containing vancomycin (6 g/mL). Enterococci were isolated on Citrate-azide tween carbonate agar supplemented with vancomycin. Species-specific PCR was performed for molecular identification of enterococci. Out of 60 fish samples screened, 47 (78.3%) samples were positive for VRE. Among VRE the prevalence % of E. casseliflavus was maximum 28/47(59.5%), followed by E. faecalis 12/47 (25.5%), E. gallinarum 4/47 (8.5%) and E. faecium 3/47 (6.3%). The VRE isolates were screened by multiplex PCR for the detection of vancomycin resistance genes. The chromosomal encoded gene vanC1 and vanC2/3 were detected both in E. faecalis and E. faecium. While, vanC2/3 gene was detected in E. casseliflavus and E. gallinarum. Notably, vanA and vanB genes were not detected in any of the VRE. Further, virulence genes (asa1, cylA, esp, gelE and hyl) or biofilm encoding gene (Ebap) were not detected in the VRE. The findings of our study indicate that vancomycin resistance in enterococci isolated from freshwater fish was mediated by chromosomal genes and not by acquired genes. VRE of freshwater fish may neither pose risk to public health nor contribute in the global spread of vancomycin resistance.